DPP‐4 Inhibitor Linagliptin Attenuates Aβ‐induced Cytotoxicity through Activation of AMPK in Neuronal Cells. (26th May 2015) - Kornelius, Edy; Lin, Chih‐Li; Chang, Hsiu‐Han; Li, Hsin‐Hua; Huang, Wen‐Nung; Yang, Yi‐Sun; Lu, Ying‐Li; Peng, Chiung‐Huei; Huang, Chien‐Ning
Summary Aim It is now clear that insulin signaling has important roles in regulation of neuronal functions in the brain. Dysregulation of brain insulin signaling has been linked to neurodegenerative disease, particularly Alzheimer's disease (AD). In this regard, there is evidence that improvement of neuronal insulin signaling has neuroprotective activity against amyloid β (Aβ)‐induced neurotoxicity for patients with AD. Linagliptin is an inhibitor of dipeptidylpeptidase‐4 (DPP‐4), which improves impaired insulin secretion and insulin downstream signaling in the in peripheral tissues. However, whether the protective effects of linagliptin involved in Aβ‐mediated neurotoxicity have not yet been investigated. Methods In the present study, we evaluated the mechanisms by which linagliptin protects against Aβ‐induced impaired insulin signaling and cytotoxicity in cultured SK‐N‐MC human neuronal cells. Results Our results showed that Aβ impairs insulin signaling and causes cell death. However, linagliptin significantly protected against Aβ‐induced cytotoxicity, and prevented the activation of glycogen synthase kinase 3β (GSK3β) and tau hyperphosphorylation by restoring insulin downstream signaling. Furthermore, linagliptin alleviated Aβ‐induced mitochondrial dysfunction and intracellular ROS generation, which may be due to the activation of 5′ AMP‐activated protein kinase (AMPK)‐Sirt1 signaling. This upregulation of Sirt1 expression was also observed in diabetic patients with AD coadministration of linagliptin. Conclusions Taken together, our findings suggest linagliptin can restore the impaired insulin signaling caused by Aβ in neuronal cells, suggesting DPP‐4 inhibitors may have therapeutic potential for reducing Aβ‐induced impairment of insulin signaling and neurotoxicity in AD pathogenesis.